Embolization of an Exophytic Posterior Neck Mass Secondary to a Cutaneous Renal Cell Carcinoma Metastasis - Dallas E. Kramer; Mena G. Kerolus; Lee A. Tan; Smita Patel; Vijaya Reddy; Michael Chen (Neurointervention, 2020)
Renal cell carcinoma (RCC) commonly metastasizes to the lung, liver, bones, and brain; however, cutaneous metastases remain rare with few reported cases. Since RCCs have the propensity to metastasize to highly vascular areas, the scalp and skin of the head and neck region are likely locations for cutaneous metastases. We report a rare case of a large, exophytic, cauliflower-like, hemorrhagic, metastatic mass of the posterior neck. This is the first reported case of a head and neck cutaneous RCC metastasis treated with endovascular embolization prior to surgical resection. Due to the increased vascularity of RCCs and risk of excessive hemorrhage during resection, adjunctive embolization of cutaneous head and neck metastasis may have a role. Essential characteristics to our treatment strategy are discussed with a review of pertinent literature.